Safety and Clinical Efficacy of Mesenchymal Stem Cell Treatment in Traumatic Spinal Cord Injury, Multiple Sclerosis and Ischemic Stroke – A Systematic Review and Meta-Analysis - Kvistad, Christopher Elnan; Kråkenes, Torbjørn; Gjerde, Cecilie; Mustafa, Kamal; Rekand, Tiina; Bø, Lars (Frontiers in Neurology, 2022)
Background Mesenchymal stem cells (MSCs) is an attractive candidate in regenerative research and clinical trials have assessed their therapeutic potential in different neurological conditions with disparate aetiologies. In this systematic review, we aimed to assess safety and clinical effect of MSC treatment in traumatic spinal cord injury (TSCI), multiple sclerosis (MS) and ischemic stroke (IS). Methods A systematic search was performed 2021-12-10 in MEDLINE, EMBASE, Web of Science and Cochrane where clinical studies assessing MSC treatment in TSCI, MS or IS were included. Studies without control group were excluded for efficacy analysis, but included in the safety analysis. For efficacy, AIS score, EDSS score and mRS were used as clinical endpoints and assessed in a meta-analysis using the random effects model. Findings Of 5548 identified records, 54 studies were included. Twenty-six studies assessed MSC treatment in TSCI, fourteen in MS and nine in IS, of which seven, seven and five studies were controlled, respectively. There were seven serious adverse events (SAEs), of which four were related to the surgical procedure and included one death due to complications following the implantation of MSCs. Three SAEs were considered directly related to the MSC treatment and all these had a transient course. In TSCI, a meta-analysis showed no difference in conversion from AIS A to C and a trend towards more patients treated with MSCs improving from AIS A to B as compared to controls (p=0.05). A subgroup analysis performed per protocol, showed more MSC treated patients improving from AIS A to C in studies including patients within 8 weeks after injury (p=0.04). In MS and IS, there were no significant differences in clinical outcomes between MSC treated patients and controls as measured by EDSS and mRS, respectively. Interpretation MSC-treatment is safe in patients with TSCI, MS and IS, although surgical implantation of MSC led to one fatal outcome in TSCI. There was no clear clinical benefit of MSC treatment, but this is not necessarily a proof of inefficacy due to the low number of controlled studies. Future studies assessing efficacy of MSC treatment should aim to do this in randomized, controlled studies.